Microstructural and creep characterization of Sn-0.7Cu and Sn-0.7Cu-xBi lead-free solders for low cost electronic applications - Alsowidy, Shakib; Aljarbani, Ahmed M.; Gumaan, Mohammed S. (Elsevier, 2022)
The microstructural, creep resistance and electrical conductivity properties of Sn-0.7 Cu eutectic alloy with Bi-additions in concentrations (0.3 and 0.5 wt.%) have been investigated using x-ray diffraction (XRD), Scanning electron microscope (SEM), creep testing machine and (DC) circuit respectively. The three samples were prepared from high purity (99.99%) elements Sn, Cu, and Bi using melting technique. XRD and SEM analysis showed that the eutectic Sn-0.7 Cu alloy composed primarily of two phases; a body centered tetragonal ??-Sn phase and monoclinic IMC Cu6Sn5, the additions of 0.3 and 0.5 wt.% Bi to the eutectic Sn-0.7 Cu promote the formation of IMC Cu6Sn5. The above motioned Bi additions have refined the ??-Sn particle size. Creep tests showed that the creep strain rate increases and the creep lifetime (rupture time) decreases as the applied stress and temperature rises. Improvements in creep resistance solders have been achieved by increasing the Bi content up to 0.5 wt.%. The mean values of stress exponent and activation energy indicate that the dislocation creep is the dominate controlling mechanism. The electrical conductivity of the samples was calculated at room temperature, it has the highest value with 0.3 wt.% of Bi.